Exploring the work to family and family to work relationship with depression on academic women employees with select demographic profile. - Rao, S.S. and Ramasundaram, Aiswarya (Abhigyan, 2009)
This study deals with the relationship and the effect of the demographic profile (namely age, number of children / dependents, education and designation with depression. Data was collected from university teaching faculty with the sample size of one hundred and twenty three. Questionnaires were distributed and statistical analysis was carried out on the collected data. Results prove that depression exists among all age groups, of number of children, educational background, number of dependents with significant differences.